1976
DOI: 10.1007/bf02544065
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects of the cyclic monomers of methyl linolenate in the rat

Abstract: Low levels (0.0075, 0.0225, and 0.15%) of cyclic fatty acid methyl esters (greater than 98% pure) were incorporated into diets of weanling rats fed different levels of protein. Animals on low protein diets (8-10% casein) exhibited decreased wt gains and feed consumption with increasing levels of cyclic esters in their diets after 6 weeks. Liver enlargements due to a significant (P less than 0.01) accumulation of liver lipid were noted in animals receiving 0.15% cyclic fatty acid esters in their diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
(27 reference statements)
2
19
1
Order By: Relevance
“…Increased liver lipid content observed with both CFAM diets in this study is consistent with the literature (Iwaoka & Perkins, 1976; Lamboni et al., 1998), but we found no significant effect of CFAM on plasma glucose and insulin. These latter results suggest that lipid accumulation in the liver might not resulted from disturbances in carbohydrate homeostasis (Adeli et al, 2001), due likely to the normal physiological state of rats used in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased liver lipid content observed with both CFAM diets in this study is consistent with the literature (Iwaoka & Perkins, 1976; Lamboni et al., 1998), but we found no significant effect of CFAM on plasma glucose and insulin. These latter results suggest that lipid accumulation in the liver might not resulted from disturbances in carbohydrate homeostasis (Adeli et al, 2001), due likely to the normal physiological state of rats used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Heated edible oils can contain up to 0.66% CFAM of total fatty acids (Frankel et al, 1984). It has been observed that diets containing CFAM increase either liver weight or hepatic lipid content compared to control diets (Iwaoka & Perkins, 1976), but the underlying mechanisms are not fully elucidated. Martin et al.…”
Section: Introductionmentioning
confidence: 99%
“…' : ' " 96 - The toxicity of feeding low levels lof cyclic monomers has been ," demonstrated in laboratory experiments with animaIs. 'Iwaoka and Perkins (1976) in experiments with rats showed that the ,.incorporatIon of low' levels (0.1)%) of purlfied cyclic fatty acid methyl esters (methyl w(2-alkyl cyclohexadlenyl) carboxyllc aClds) in diets which contained 8%…”
Section: ' "mentioning
confidence: 99%
“…Iwaoka and Perkins (11) showed that when small quantities (about 1%) of purified methyl ω-(2-alkyl cyclohexyl) carboxylic acids (CFAME) were fed to rats with lowlevel protein diets (8-10% casein), the CFAME decreased weight gains and feed consumption in these animals compared to controls. Liver enlargement with accumulation of lipid was detected in animals fed 0.15% CFAME in their diets.…”
mentioning
confidence: 98%